Building Teaching-Learning Capacities of Online Nurse Educators: Using TPACK to Frame Pedagogical Processes and Identify Required Supports - Kraglund-Gauthier, Wendy; Moseley, Jane (Canadian journal of learning and technology, 2019)
Quality teaching includes reflective practice, dialogue, and curiosity and depends on personal, institutional, and community assets and constraints, as well as on the individual's definitions of the roles of education in society. Based on an environmental scan and action research with instructors in an online distance Bachelor of Science, Nursing program for registered nurses, participants identified five "big ideas" involving community, instructors, class, interpersonal relationships, and supports to build capacity around the three elements of technological pedagogical content knowledge, or TPACK (Koehler, Mishra, Akcaoglu, & Rosenberg, 2013).